Nonlinear association between red cell distribution width/albumin ratio and peripheral arterial disease in the NHANES: a cross-section study with propensity score matching analysis - Jinmin Cao; Zhixiong Deng; Li Xiang; Feng Wang; Ting Yang (Frontiers in Cardiovascular Medicine)
BackgroundPeripheral arterial disease (PAD) is a prevalent cardiovascular condition that affects up to 200 million people globally, and has significant implications for morbidity and mortality. Recent studies have identified the red cell distribution width-to-albumin ratio (RDW/ALB) as a potential systemic inflammatory marker that is correlated with several cardiovascular and inflammatory diseases including PAD. However, the comprehensive role of RDW/ALB in PAD remains underexplored. The objective of this study was to elucidate the relationship between RDW/ALB and PAD and to provide novel insights into the prevention and treatment of PAD.MethodsThis retrospective cross-sectional study leveraged data from the NHANES data (1999–2004) identifying PAD using ankle-brachial index measurements (<0.90). The association with PAD was assessed using multivariable logistic regression, complemented by a restricted cubic spline for nonlinearity, and propensity score methods for robustness checks, including propensity score matching and subgroup analyses.ResultsThis study included 6,421 participants, 452 of whom had PAD. The mean age was 70.1 years; the patients were predominantly male. After adjustment, the RDW/ALB ratio showed a significant association with PAD (OR 1.71, 95% CI 1.29–2.26, p < 0.001). After quartiles of RDW/ALB, the risk of PAD was determined to be 2.03 (95% CI 1.31–3.14) in the Q4 group compared with the Q1 group in the adjusted complete model. The restricted sample cubic spline of RDW/ALB and risk of developing PAD demonstrated a nonlinear relationship. The risk of PAD increased considerably with higher RDW/ALB ratios less than 4.08. Subgroup and PSM analyses underscored the consistency of these findings.ConclusionsThe study demonstrated a significant association between RDW/ALB and PAD, with a nonlinear relationship and a threshold effect. Further prospective clinical research is required to validate the relationship between the RDW/ALB ratio and PAD.